POST-PANDEMI COVID-19 BREAD MSME MARKETING STRATEGY - Herdiana Dyah Susanti; Dian Arief Pradana; Mahfud Mahfud (International Journal of Artificial Intelligence Research, 2022)
The covid-19 pandemic has had an impact on life as well as business. Good marketing means having a deep understanding of potential customers where many potential customers have changed due to the Covid-19 pandemic. The company needs to analyze the different marketing channels it currently has in the market and focus more on the channels that get more customer attention. The development of MSMEs in the culinary field in Banyuwangi is currently starting to develop. One of them is UMKM that produces home-made bread, namely Jessica Bakery. As many home-baked MSMEs have emerged, entrepreneurs are required to be more creative in designing and deciding on marketing strategies to be implemented in order to compete. The aim of this study is to find out the best alternative marketing strategies that can be used in UMKM "Jessica Bakery". The method used is a SWOT analysis which aims to determine the location of the company and the Analytical Hierarchy Process (AHP) is used to determine the best marketing strategy for UMKM Jessica Bakery. The results of the study based on the SWOT analysis found that Jessica Bakery's UMKM was located in quadrant I by implementing the SO (Strength-Opportunity) strategy and through the Analytical Hierarchy Process (AHP) method, eight alternative marketing strategies were produced. The best marketing strategy is alternative two, namely maximizing the use of social media as a marketing tool with a value weight of 0.1328.